Advances in technology and techniques for transcatheter aortic valve replacement with concomitant peripheral arterial disease - Wong, Chun-Ka; Chiu, Alston Conrad Ho-On; Chan, Kwong-Yue Eric; Sze, Shu-Yue; Tam, Frankie Chor-Cheung; Un, Ka-Chun; Lam, Simon Cheung-Chi; Tse, Hung-Fat (Frontiers in Medical Technology, 2022)
Aortic stenosis (AS) is a prevalent disease affecting 3.7% of the adult population aged 65 or above. In the past, surgical aortic valve replacement (SAVR) was the only definitive therapy available for the treatment of severe AS. Owing to the invasive nature of open-heart surgery, patients with advanced age and frailty could not benefit from SAVR. The advent of transcatheter aortic valve replacement (TAVR) in the past decade has offered an alternative treatment option for patients with severe AS, particularly those who are deemed to have high surgical risks. Nevertheless, a large proportion of patients also have concomitant peripheral arterial disease (PAD), which increases the risk of peri-procedural vascular complication, and precludes the possibility of transfemoral TAVR owing to inadequate luminal size for delivery system deployment. In this review, the prevalence and outcome of TAVR patients with PAD will be discussed. Furthermore, novel technologies and techniques that enable TAVR to be safely performed using transfemoral or alternative access in patients with severe PAD will be reviewed.